Communicating marine climate change impacts in the Caribbean and Pacific regions. (January 2020) - Townhill, Bryony L; Hills, Jeremy; Murray, Peter A; Nichols, Keith; Pringle, Paddy; Buckley, Paul
Abstract: The scientific literature on marine and coastal climate change has proliferated in recent decades. Translating and communicating this evidence in a timely, and accessible manner, is critical to support adaptation, but little is being done to summarise the latest science for decision makers. For Small Island Developing States (SIDS), which are highly vulnerable to marine and coastal climate change impacts, there is an urgent need to make the latest science readily available to inform national policy, leverage climate funding and highlight their vulnerability for international reports and climate negotiations. Climate change report cards are a proven successful way of presenting climate change information in an easily accessible and informative manner. Here we compare the development of marine climate change report cards for Caribbean and Pacific Commonwealth SIDS as a means of translating the latest science for decision makers. Regional engagement, priority issues and lessons learnt in these regions are compared, and future opportunities identified. Highlights: Communicating accurate climate change information is vital for small islands. This is needed to effectively inform national policy and adaptation. Regional marine climate change report cards are one way of doing this. The cards have a big impact internationally and regionally. They communicate priorities for climate action.